Review of Toby Lincoln, An Urban History of China - Jackson, Isabella (My University, 2023)
Perhaps the greatest achievement of this book is the way that Toby Lincoln manages to convey a great enthusiasm for the vibrancy of Chinese cities. Author and reader alike are seduced by these exciting concentrations of humanity where government was concentrated, societal change was accelerated, culture was nurtured, commerce and crime flourished and religion and ideology were played out physically in the architecture and design of public space. To convey the thrilling energy of Chinese cities is particularly impressive in a textbook format, covering a vast stretch of time – the best part of four thousand years – and geography in an accessible style. Significant amounts of information are conveyed clearly, with the crucial knowledge students need to understand urban development and life in China alongside telling details that enliven what could be a dense read. We are invited to picture nine chariots side-by- side ‘thundering past, splattering pedestrians with mud on a rainy day’ to appreciate the urban plan dictating such wide thoroughfares (p. 40) and read contemporary accounts of ‘onlookers as dense as threads in a cloth’ enjoying the spectacle of elephants in imperial processions (p. 95).
An Urban History of China
Keywords: Identities in Transformation; International Development; Manuscript, Book and Print Cultures; Chinese History; Urban History; Urban and economic history; History